The Effect of Shariah Committee Composition on Malaysian Islamic Banks’ Audit Report Lag - Uyob, Suzilawati; Zin, Ana Salwa Md; Ramli, Junaira; Othman, Jaizah; Ghani, Nur Amalina Abdul; Salleh, Kalsom (International Journal of Applied Economics, Finance and Accounting, 2022)
Financial reporting is one of the primary sources of information about a company. Financial reports must be issued on time to ensure that the users of financial information receive them on time to allow them to make decisions. Delays in issuing financial reports interfere with users of financial information making decisions. This research aimed to identify the effect of Shariah committee composition on the audit report lag of Malaysian Islamic banks. The study quantitatively analysed the financial reporting of 16 Islamic banks in Malaysia from 2011 to 2020. The analysis revealed that Shariah committee expertise and meeting frequency had significant relationships with audit delay. However, Shariah committee independence and size displayed insignificant relationships. The study's findings support the agency theory hypothesis. The results suggest that principal and agent conflict can be relieved by equipping more members of the Shariah committee with accounting and financial knowledge.